Distinct clinical patterns and immune infiltrates are observed at time of progression on targeted therapy versus immune checkpoint blockade for melanoma. (3rd March 2016) - Cooper, Zachary A.; Reuben, Alexandre; Spencer, Christine N.; Prieto, Peter A.; Austin-Breneman, Jacob L.; Jiang, Hong; Haymaker, Cara; Gopalakrishnan, Vancheswaran; Tetzlaff, Michael T.; Frederick, Dennie T.; Sullivan, Ryan J.; Amaria, Rodabe N.; et al.
ABSTRACT: We have made major advances in the treatment of melanoma through the use of targeted therapy and immune checkpoint blockade; however, clinicians are posed with therapeutic dilemmas regarding timing and sequence of therapy. There is a growing appreciation of the impact of antitumor immune responses to these therapies, and we performed studies to test the hypothesis that clinical patterns and immune infiltrates differ at progression on these treatments. We observed rapid clinical progression kinetics in patients on targeted therapy compared to immune checkpoint blockade. To gain insight into possible immune mechanisms behind these differences, we performed deep immune profiling in tumors of patients on therapy. We demonstrated low CD8 + T-cell infiltrate on targeted therapy and high CD8 + T-cell infiltrate on immune checkpoint blockade at clinical progression. These data have important implications, and suggest that antitumor immune responses should be assessed when considering therapeutic options for patients with melanoma.